2006
DOI: 10.1016/j.nuclphysb.2006.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Twisted D-branes of the WZW model and level-rank duality

Abstract: We analyze the level-rank duality of ω c -twisted D-branes of su(N ) K (when N and K > 2). When N or K is even, the duality map involves Z Z 2 -cominimal equivalence classes of twisted D-branes. We prove the duality of the spectrum of an open string stretched between ω c -twisted D-branes, and ascertain the relation between the charges of level-rank-dual ω c -twisted D-branes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…To conclude this section, we finally mention level‐rank dualities, which are certain mysterious relations between WZW theories that involve swapping a parameter for the group with one for the Virasoro level (see, for example, .) This is quite a deep subject and does seem to be connected with twisted K‐theory calculations, though not in a totally straightforward way.…”
Section: Langlands Duality and The Twisted K‐theory Of Simple Compactmentioning
confidence: 99%
“…To conclude this section, we finally mention level‐rank dualities, which are certain mysterious relations between WZW theories that involve swapping a parameter for the group with one for the Virasoro level (see, for example, .) This is quite a deep subject and does seem to be connected with twisted K‐theory calculations, though not in a totally straightforward way.…”
Section: Langlands Duality and The Twisted K‐theory Of Simple Compactmentioning
confidence: 99%
“…We defined a one-to-one map α → α between the spinor ε-twisted D-branes of so(2n) 2k and the spinor ε-twisted D-branes of so(2k) 2n . We then showed that the multiplicity n β In both the su(N) K and sp(n) k WZW theories, the charges of level-rank-dual untwisted D-branes are equal (modulo sign) [5,6], with a slightly more complicated relationship holding between the charges of twisted D-branes [7]. In the case of so(N) K , however, the charges of the D-branes do not exhibit any simple relationship under level-rank duality.…”
Section: Discussionmentioning
confidence: 99%
“…In both the su(N) K and sp(n) k WZW theories, the charges of level-rank-dual untwisted D-branes are equal (modulo sign) [5,6], with a slightly more complicated relationship holding between the charges of twisted D-branes [7]. In the case of so(N) K , however, the charges of the D-branes do not exhibit any simple relationship under level-rank duality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations